RELATION OF THREE-TIME POINT ESTIMATION OF INFLAMMATORY MARKERS WITH THE SEVERITY AND OUTCOME IN PATIENTS OF COVID-19 IN A TERTIARY CARE HOSPITAL OF PESHAWAR - Hussain, Munir; Orakzai, Sheryar; Mirza M Dawood; Aamir Ijaz; Noman Shah; Saiqa Zahoor (Journal of Postgraduate Medical Institute, 2024)
Objective: To assess the correlation of different time point estimations of inflammatory markers of Covid-19 with the severity and outcome of the disease. Methodology: This study was conducted from December 2021 to May 2022 in the covid-19 ward/ICU of Rehman Medical Institute, Peshawar. Total 116 adult subjects from both genders were included in study. Three-time point estimation of markers for the assessment of severity and outcome of disease was done. Patients were divided into deceased and recovered categories on outcome and into mild, moderate, severe, and critical categories on disease severity basis. Results: Three-time point estimation of markers on outcome basis showed that all the markers were significantly higher in deceased subjects as compared to recovered ones. Three-time point estimation according to disease severity revealed that all the markers were higher in critically ill as compared to mildly ill patients. Similarly, majority of the markers were higher in severe as compared to mild, and higher in critical as compared to moderate categories. On ROC curve analysis of markers on admission, only lactate dehydrogenase (LDH) had a good AUC. On multivariable logistic regression analysis after adjustment for covariates, old age, LDH, neutrophil-lymphocyte ratio (NLR), diabetes mellitus (DM) and ischemic heart disease (IHD) predicted the mortality. Conclusion: LDH, white blood cell (WBC) count, and NLR based on three-time point estimation correlated with morbidity and mortality. Old age, NLR, and LDH on admission, and comorbidities like DM and IHD were significantly associated with mortality.